Study on the influence of natural cracks on the mechanical properties and fracture mode for shale at the microscale: An example from the Lower Cambrian Niutitang Formation in northern Guizhou - Yang, Chao; Wu, Zhonghu; Wang, Wentang; Qu, Heng; Ren, Nuo; Li, Hai (Frontiers in Earth Science, 2023)
A large number of natural cracks exist in shale reservoirs, and the presence of natural cracks weakens the integrity of shale, which is an important factor governing the effectiveness of shale gas extraction. In this paper, shales from the Lower Cambrian Niutitang Formation in northern Guizhou were scanned by electron microscopy, their microstructures were selected for digital image processing, and uniaxial compression numerical tests were conducted on shale models containing different natural crack dips using the rock fracture process system RFPA2D-DIP to study the effects of natural cracks on the mechanical properties and fracture patterns of shales at the microscopic scale. The study shows that the peak strength and elastic modulus of shale increase with increasing natural crack inclination angle. The fracture modes of shale at the microscopic scale can be roughly divided into four categories: similar to I-type fractures (0°), oblique I-type fractures (15°, 45°, 60°, 75°), folded line fractures (30°), and V-type fractures (90°). Natural cracks within shale are found to have a significant effect on the distribution of stress. Acoustic emission can reflect the stress change and rupture process for shales containing natural cracks with different dip angles at the microscopic scale. The presence of natural cracks has a significant effect on the AE energy and fractal dimension. The magnitude of the AE energy increases with increasing stress level and reaches a maximum value at 90°, while the value of the fractal dimension is found to zigzag upwards because the value of the fractal dimension is jointly influenced by both newborn cracks and native natural cracks.